PEMANFAATAN PANEL SURYA DAN GREENHOUSE SEBAGAI SOLUSI PERTANIAN MODERN DI GANG HIJAU SWAKARYA - Dian Rusdiyanto; Dian Widi Astuti; Galang Persada Nurani Hakim; Ahmad Firdausi; Freddy Artadima Silaban; Agung Wahyudi Biantoro (Jurnal Abdi Insani, 2026)
This Community Service Program was conducted at Gang Hijau Swakarya Hydroponic Garden, Meruya Selatan Urban Village, Kembangan District, West Jakarta, with the aim of improving energy independence and urban agricultural productivity through the application of renewable energy technology and environmentally based crop protection systems. The activity began with a field observation to identify the main problems faced by the partner, namely a damaged solar power system and an open garden area without adequate protection from pests and dust. As a solution, the solar panel system was repaired and upgraded from six non-functional 100 Wp modules to eight 100 Wp modules, accompanied by the replacement of the panel box and the installation of two 12.8 V 100 Ah LiFePO₄ batteries connected in parallel to increase energy storage capacity. In addition, a 2 m × 11 m greenhouse covered with insect netting was constructed to maintain stable plant growth and protect crops from pest attacks and dust exposure. The program continued with training and mentoring for the partner and local community, covering an introduction to the solar panel system and hydroponic cultivation management. The questionnaire results showed an increase in participants’ knowledge and satisfaction regarding the use of solar energy and greenhouse construction. As the closing activity, the handover of the 2025 Kemdiktisaintek grant assets was conducted and witnessed by the Head of Meruya Selatan Urban Village.